Vitamin D in Thyroid Disorders - Kmieć, P.; Sworczak, K. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Vitamin D’s canonical role are its effects exerted on the musculoskeletal system. In the last decades the importance of this hormone has been studied in the context of extraskeletal health. Hypovitaminosis D and several polymorphic variants of genes coding proteins crucial in the transport, metabolism and effects of vitamin D have been associated with negative health outcomes.In this review the current state of knowledge on the role of vitamin D in thyroid disorders is presented. The review is based on a literature search of the PubMed database performed in December 2014. The following search terms were used in conjunction with ‘vitamin D’: thyroid cancer, Graves’, Hashimoto, thyroiditis, autoimmune thyroid, AITD, nodules, hyperthyroidism, and hypothyroidism.Currently, similarly to other extraskeletal health outcomes, a clear role of vitamin D has not been demonstrated in thyroid disorders. Further research is necessary to fully elucidate the importance of vitamin D in case of thyroid disease.
Keywords: vitamin D; vitamin D deficiency; calcitriol; thyroid cancer; autoimmune thyroiditis; Graves’ disease; Hashimoto thyroiditis; hyperthyroidism; hypothyroidism